Repetition’s Poeticity in Abe Al-Kasem Al-Shabe’s Collection of Poems - Nemer, Mostafa; Hussein, Mohammed (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aims at dealing with repetition’s poeticity in Abe Al-Kasem Al-Shabe’s collection of poems, that phenomenon appeared clearly in his poetry which is closely connected with the poet’s psyche and helps in building in his life. This repetition depends on a group of stylistic choices to a specific subject and to a specific linguistic formula. This reveals eventually the secret behind the poet’s trend to this stylisitic genre not another. The research also tries to identify with repetition types used by Abe Al0Kasem Al-Shabe represented in repeating the letter, the verb, the word, the pronoun, the sentence, the verse, the stanza and the creative repetition. It also tries to identify with the role of these points in building a sentnece with its different types. It also aims at knowing to which degree those points were able to to make new poetic contexts which have stronge meanings for the receiver and which in its turn work on attracting his attention to live within the poetic state which is portrayed by the poet himself.The research also reveals the accurate structure of this repetition resulted from Al-Shabe’s genuisity in the artisitic poetic text.